Indirect Application of Intense Pulsed Light Induces Therapeutic Effects on Experimental Murine Meibomian Gland Dysfunction - Xie, Luoying; Song, Wenjing; Dong, Wenhui; Li, Yingsi; Chen, Shudi; Sun, Xiaona; Huang, Meiting; Cheng, Yu; Gao, Yuan; Yang, Songlin; Yan, Xiaoming (Frontiers in Medicine, 2022)
Purpose: To investigate the indirect effects of intense pulsed light (IPL) on morphological and pathological changes of the meibomian glands (MGs) in apolipoprotein E knockout (ApoE-/-) mice and explore the underlying mechanisms. Methods: ApoE-/- mice were treated with or without IPL three times below the lower eyelids and MGs were not directly exposed to irradiation. The eyelids and ocular surface were observed under a stereoscope. The morphology of MGs was examined by photographing and hematoxylin & eosin staining. Lipid droplets in MGs were examined by Oil Red O staining. The ultrastructure of meibocytes and mitochondria was observed under transmission electron microscopy. The relative gene and protein expression in MGs of upper eyelids was determined by immunostaining, Western blot, and qRT–PCR. Results: Three IPL treatments decreased the toothpaste-like plugging of orifices and thickening and irregularity of the upper and lower eyelid margins in ApoE-/- mice. The morphology of some MGs improved after IPL treatments, accompanied by increased proliferation of acinar basal cells and decreased ductal keratinization. Furthermore, the accumulation of hyperchromatic lipid droplets in the acini increased, and the lipid droplets distributed in the cells around the acini were round and small. Compared with untreated ApoE-/- mice, oxidative stress and apoptosis were downregulated by IPL treatment, accompanied by the improvements in mitochondrial structure. Further research showed that IPL treatments reduced the levels of tumor necrosis factor-alpha (TNF-α), interleukin (IL)-17A, IL-6 in MGs and inactivated nuclear factor kappa B (NF-κB). Conclusion: Collectively, the results demonstrate that indirect effects of IPL can improve the structure and function of MGs and mitigate the progression of MGD, which may be related to the indirect effects of photobiomodulation.